2019
DOI: 10.3390/molecules24122205
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol Effects on Splenic Cytokine Response in Post-Weaning Contactin 1-Overexpressing Transgenic Mice

Abstract: Background: In mice, postnatal immune development has previously been investigated, and evidence of a delayed maturation of the adaptive immune response has been detected. Methods: In this study, the effects of red grape polyphenol oral administration on the murine immune response were explored using pregnant mice (TAG/F3 transgenic and wild type (wt) mice) as the animal model. The study was performed during pregnancy as well as during lactation until postnatal day 8. Suckling pups from polyphenol-administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Our findings revealed low basal levels of circulating cytokines/chemokines and a delayed immune response in rats on a pre-emptive enriched Mediterranean-like diet post-ischemia. The spleen, which is crucial in post-damage adaptive immune responses, including ischemia [60,61], appears to be positively influenced by this diet, as supported by previous studies [62,63]. Interestingly, previous studies showed that either the pre-tMCAO removal of the spleen or its post-tMCAO irradiation results in lower infarct volumes and white blood cell counts [64][65][66].…”
Section: Discussionsupporting
confidence: 55%
“…Our findings revealed low basal levels of circulating cytokines/chemokines and a delayed immune response in rats on a pre-emptive enriched Mediterranean-like diet post-ischemia. The spleen, which is crucial in post-damage adaptive immune responses, including ischemia [60,61], appears to be positively influenced by this diet, as supported by previous studies [62,63]. Interestingly, previous studies showed that either the pre-tMCAO removal of the spleen or its post-tMCAO irradiation results in lower infarct volumes and white blood cell counts [64][65][66].…”
Section: Discussionsupporting
confidence: 55%
“…Conversely, 00123A7 did not exhibit any significant effect. Previous studies have already provided evidence that certain (poly)phenols are able to induce IL-10 release, as some found in red grapes [ 32 ] or green tea [ 33 ], but this is the first report of raspberry (poly)phenols exhibiting such an effect. Thereby, we conclude that the higher levels of ETs, ET degradation products and EA derivatives in the 2J19 GIB sample not only attenuate pro-inflammatory markers, but also are capable of inducing a direct anti-inflammatory action by inducing IL-10 release, hampering microglial pro-inflammatory cascades as the inflammasome ( Figure 2 E).…”
Section: Resultsmentioning
confidence: 88%
“…Our study has found important data showing basal low levels of circulating cytokines/chemokines and a delayed immune response in rats fed on enriched Mediterranean-like diet following ischemic damage. It is well-known that the spleen is the largest secondary lymphoid organ with a major role in the induction of adaptive immune responses following damage, including ischemia [71,72] and, interestingly, some studies have suggested that either a Mediterranean diet [73] or polyphenols [24,74] has a positive immunomodulatory effect on the spleen. Interestingly, previous studies showed that either the pre-tMCAO removal of the spleen or its post-tMCAO irradiation results in lower infarct volumes and white blood cell counts [75][76][77].…”
Section: Discussionmentioning
confidence: 99%